2012
DOI: 10.1017/s095026881200194x
|View full text |Cite
|
Sign up to set email alerts
|

Colistinvs. the combination of colistin and rifampicin for the treatment of carbapenem-resistantAcinetobacter baumanniiventilator-associated pneumonia

Abstract: The aim of this study was to compare the responses of colistin treatment alone vs. a combination of colistin and rifampicin in the treatment of ventilator-associated pneumonia (VAP) caused by a carbapenem-resistant A. baumannii strain. Forty-three patients were randomly assigned to one of two treatment groups. Although clinical (P = 0·654), laboratory (P = 0·645), radiological (P = 0·290) and microbiological (P = 0·597) response rates were better in the combination group, these differences were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(168 citation statements)
references
References 29 publications
4
155
1
8
Order By: Relevance
“…This result is in agreement with a previous Egyptian study by Al-Agamy et al, 2014who reported that the percentage of colistin susceptibility was 95%. Also our finding is consistent with the finding of other studies that reported A. baumannii isolates were100% sensitive to colistin such as Fouad et al, (2013), Josheghani et al, (2016), Cherkaoui et al, (2015), Cicek et al, (2013), Abdalhamid et al, (2014).There is tendency to increase using colistin in treatment of VAP caused by A. baumannii as it currently most effective drug (Aydemir et al, 2013;Jean & Hsueh, 2011). The colistin resistance rate is relatively low may be because its infrequent use (Al-Agamy et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…This result is in agreement with a previous Egyptian study by Al-Agamy et al, 2014who reported that the percentage of colistin susceptibility was 95%. Also our finding is consistent with the finding of other studies that reported A. baumannii isolates were100% sensitive to colistin such as Fouad et al, (2013), Josheghani et al, (2016), Cherkaoui et al, (2015), Cicek et al, (2013), Abdalhamid et al, (2014).There is tendency to increase using colistin in treatment of VAP caused by A. baumannii as it currently most effective drug (Aydemir et al, 2013;Jean & Hsueh, 2011). The colistin resistance rate is relatively low may be because its infrequent use (Al-Agamy et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…[5] In contrast, two randomised controlled trials found no difference in mortality and cure rates despite the higher microbiological eradication rate with combined therapy, when comparing colistin and colistin-rifampicin for treating VAP and several severe infections. [3,21,22] Another study reported no clinical or statistical difference between monotherapy and combined therapy for the treatment of MDR-AB infections, and indicated that use of monotherapy would be reasonable for at least treating less severe infections. [3] The same study suggested that drug choice can be customised according to drug access, drug interactions, side-effects and costs, since there is no difference between the drugs in resistant A. baumannii pneumonia reported to be hospital acquired or ventilator associated.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were treated with CMS (Colimycin  , Kocak Farma, Turkey; each vial contained 150 mg colistin base activity, which is approximately equivalent to 360 mg, or 5 million IU of CMS), which is the only available form of colistin in Turkey (9)(10)(11). Although the prospectus recommendation of IV dosages for CMS is 2.5-5 mg/kg/day (base activity), divided into 2-4 doses for normal renal function, it is usually administered in fixed doses equivalent to 300 mg or 450 mg/day, divided into 2 or 3 doses per day, according to the manufacturer's recommendations in Turkey.…”
Section: Methodsmentioning
confidence: 99%